Genome-Wide Association Study for Adult-Plant Resistance to Stripe Rust in Chinese Wheat Landraces (Triticum aestivum L.) From the Yellow and Huai River Valleys - Long, Li; Yao, Fangjie; Yu, Can; Ye, Xueling; Cheng, Yukun; Wang, Yuqi; Wu, Yu; Li, Jing; Wang, Jirui; Jiang, Qiantao; Li, Wei; Ma, Jian; et al. (Frontiers in Plant Science, 2019)
Stripe rust (also known as yellow rust), caused by the pathogen Puccinia striiformis f. sp. Tritici (Pst), is a common and serious fungal disease of wheat (Triticum aestivum L.) worldwide. To identify effective stripe rust resistance loci, a genome-wide association study was performed using 152 wheat landraces from the Yellow and Huai River Valleys in China, with Diversity Arrays Technology and simple sequence repeat markers. Phenotypic evaluations of resistance levels to stripe rust at the adult-plant stage under field conditions were carried out in five environments. In total, 19 accessions displayed stable, high levels of resistance to stripe rust development when exposed to mixed races of Pst at the adult-plant stage in multi-environment field assessments. A marker-trait association analysis indicated that 51 loci were significantly associated with adult-plant resistance to stripe rust. These loci speculated 40 quantitative trait loci (QTL) regions for adult-plant resistance, 20 identified resistance QTL were linked closely to previously reported yellow rust resistance genes or QTL regions, which are distributed across wheat chromosomes 1B, 1D, 2A, 2B, 3A, 3B, 4A, 4B, 5B, 6B, 7A, 7B, and 7D. Six multi-trait QTL were detected on chromosomes 1B, 1D, 2B, 3A, 3B, and 7D. With the other 20 mapping to chromosomes 1D, 2A, 2D, 4B, 5B, 6A, 6B, 6D, 7A, 7B, and 7D, far from previously identified yellow rust resistance genes. Consequently, these QTL could potentially be novel loci for stripe rust resistance. Among the potentially 20 novel QTL, 5 (QDS.sicau-2A, QIT.sicau-4B, QDS.sicau-4B.2, QDS.sicau-6A.3, and QYr.sicau-7D) were detected as being associated with field responses at the adult-plant stage in at least two environments, and may have largely effects on stripe rust resistance. The new effective QTL for adult-plant resistance to stripe rust will increase our understanding of the genetic mechanisms that control the spread of stripe rust, and will aid in the molecular marker-assisted selection-based breeding of wheat.